Probing the strength of light–matter interaction in semiconductor microcavities by using resonant-mode shifts in temperature-dependent photoluminescence spectra - Sheng-Chan Wu; Chung-Xian Yang; Jer-Shing Huang; Yia-Chung Chang; Ching-Hang Chien; Hsu-Cheng Hsu (APL Materials, 2023)
The Rabi-splitting energy represents the strength of light–matter interaction. This quantity is a good benchmark for evaluating the performance of light-modulation devices. Herein, we adopt ZnO microrods as microcavities for whispering gallery modes and propose a convenient method for estimating the light–matter coupling strength based on the shifts of resonant modes in temperature-dependent photoluminescence spectra from 295 to 77 K. Both temperature-dependent index dispersion and Rabi splitting can be extracted. Additionally, the Rabi-splitting energy of bulk ZnO at 0 K is estimated to be about 289 meV.